PERIOD CHANGE IN THE CONTACT SYSTEM AW UMA - Pribulla, T.; Chochol, D. (Одеські астрономічні публікації, 2017)
Nine new minima were determined from the UBV photoelectric observations obtained in 1992 and 1995-6. They were used to derive the new ephemerides of AW UMa. The mid-eclipse brightening best visible in U colour was detected. Possible reasons of the observed orbital period decrease are discussed.